Atmospheric Gravity Waves in Aeolus Wind Lidar Observations. Issue 10 (19th May 2021) - Banyard, T. P.; Wright, C. J.; Hindley, N. P.; Halloran, G.; Krisch, I.; Kaifler, B.; Hoffmann, L.
Abstract: Aeolus is the first Doppler wind lidar in space. It provides unique high‐resolution measurements of horizontal wind in the sparsely observed upper‐troposphere/lower‐stratosphere (UTLS), with global coverage. In this study, Aeolus' ability to resolve atmospheric gravity waves (GWs) is demonstrated. The accurate representation of these small‐scale waves is vital to properly simulate dynamics in global weather and climate models. In a case study over the Andes, Aeolus GW measurements show coherent phase structure from the surface to the lower stratosphere, with wind perturbations >10 ms −1, a vertical wavelength ∼8 km, and an along‐track horizontal wavelength ∼900 km. Good agreement is found between Aeolus and co‐located satellite, ground‐based lidar and reanalysis data sets for this example. Our results show that data from satellites of this type can provide unique information on GW sources and propagation in the UTLS, filling a key knowledge gap that underlies known major deficiencies in weather and climate modeling. Plain Language Summary: Gravity waves are an important driver of the global atmospheric circulation, but are difficult to observe due to their scale size and location. Existing satellite observations reveal these waves in temperature perturbations, but tend to be limited in either vertical or horizontal resolution. Since they are, arguably, best described in a wind‐based mathematical framework, and due to their influential behavior in the upper‐troposphere lower‐stratosphere region, an observing platform that satisfies both of these requirements could prove very significant. This study explores the capability of the first Doppler wind lidar in space, Aeolus, to measure gravity waves and provide unique information about their sources and propagation through the atmosphere. Significantly, Aeolus measures wind speed directly and is well suited to observe the upper‐troposphere lower‐stratosphere region. Here, a case study is presented showing observations of a strong gravity wave produced by the enhanced orography of the Southern Andes, which are the most prominent hotspot of gravity wave activity globally. Results are validated against two other observational instruments and atmospheric reanalysis, and give confidence in Aeolus' ability to measure these phenomena. Key Points: First satellite observations of atmospheric gravity waves using Aeolus A case study is presented of an orographic gravity wave over the Southern Andes with coherent phase structure down to the surface Results reproduce well in satellite observations and reanalysis data